2014
DOI: 10.1097/aln.0000000000000102
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasound Predicts Interstitial Syndrome and Hemodynamic Profile in Parturients with Severe Preeclampsia

Abstract: In parturients with severe preeclampsia, lung ultrasound detects both pulmonary edema and increased left ventricular end-diastolic pressures. The finding of a B-pattern should restrict the use of fluid. However, these preliminary results are associations from a single sample. They need to be replicated in a larger, definitive study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 62 publications
1
87
1
1
Order By: Relevance
“…Pediatrics 2014;134:e1089-e1094 Accepted for publication Jul 24, 2014 Chest ultrasound has recently been applied with success in different settings of adult medicine, ranging from cardiopulmonary emergencies and trauma surgery to the care of preeclamptic women or patients with renal failure. [1][2][3][4] A systematic ultrasound semeiology has been validated across a wide span of ages using both chest anatomic structures (ie, the ribs or the pleural line) and artifactual images, such as the B-lines, that are discrete, laserlike vertical hyperechoic reverberations arising from the pleural line. Multiple diffuse bilateral B-lines are suggestive of interstitial syndrome (eg, pulmonary edema, interstitial pneumonia, diffuse parenchymal lung disease) 5 (Fig 1A).…”
Section: Discussionmentioning
confidence: 99%
“…Pediatrics 2014;134:e1089-e1094 Accepted for publication Jul 24, 2014 Chest ultrasound has recently been applied with success in different settings of adult medicine, ranging from cardiopulmonary emergencies and trauma surgery to the care of preeclamptic women or patients with renal failure. [1][2][3][4] A systematic ultrasound semeiology has been validated across a wide span of ages using both chest anatomic structures (ie, the ribs or the pleural line) and artifactual images, such as the B-lines, that are discrete, laserlike vertical hyperechoic reverberations arising from the pleural line. Multiple diffuse bilateral B-lines are suggestive of interstitial syndrome (eg, pulmonary edema, interstitial pneumonia, diffuse parenchymal lung disease) 5 (Fig 1A).…”
Section: Discussionmentioning
confidence: 99%
“…27,38,40,53,57 Interestingly E/e′ was shown to be significantly higher in an early-onset preeclampsia subgroup compared with a late-onset subgroup. 40 One study used a composite of diastolic indices to diagnose diastolic dysfunction and demonstrated diastolic dysfunction in 40% of pregnancies complicated by preeclampsia at term, compared with 14% of controls.…”
Section: Diastolic Functionmentioning
confidence: 99%
“…The use of different calculations (based either on Doppler or volume calculation) is likely to contribute to the disparity for this parameter. There was similar variability with regard to LV ejection fraction, with the majority of studies showing no significant difference compared with normotensive pregnant women 30,38,52,56,57 and only 1 showing a decrease. 33 Myocardial performance index was reduced in a study of women with preeclampsia and fetal growth restriction in the third trimester.…”
mentioning
confidence: 92%
See 2 more Smart Citations